2016
DOI: 10.1186/s13063-016-1680-y
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting to Clinical Trials on the Telephone – a randomized controlled trial

Abstract: BackgroundInformed consent is an essential element of clinical research. Obtaining consent, however, may be challenging. The use of the telephone for giving information and obtaining consent may be practical but little formal research has been done.MethodsWe examined the use of the telephone for the purpose of informing expectant mothers about The Danish Calmette Study; a randomized clinical trial assessing neonatal Bacille Calmette-Guérin vaccination. Expectant mothers received an invitation letter with a Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
2
0
2
Order By: Relevance
“…Of the 80 included pediatric recruitment studies, only 1 was a randomized controlled trial. 14 Similar to our findings with pediatric recruitment strategies, a previous review of recruitment strategies for adult trials by Treweek et al 4 demonstrated a large array of strategy recommendations but few that had been rigorously validated. Importantly, the authors of this comprehensive review were unable to identify any pediatric recruitment intervention studies meeting inclusion criteria and commented on the dearth of evidence addressing recruitment to pediatric trials.…”
Section: Discussionsupporting
confidence: 86%
“…Of the 80 included pediatric recruitment studies, only 1 was a randomized controlled trial. 14 Similar to our findings with pediatric recruitment strategies, a previous review of recruitment strategies for adult trials by Treweek et al 4 demonstrated a large array of strategy recommendations but few that had been rigorously validated. Importantly, the authors of this comprehensive review were unable to identify any pediatric recruitment intervention studies meeting inclusion criteria and commented on the dearth of evidence addressing recruitment to pediatric trials.…”
Section: Discussionsupporting
confidence: 86%
“…When developing our novel framework, we found that the interventions included in our synthetic analysis leveraged a broad range of behavioral strategies beyond financial incentives to boost research participant engagement. Strategies ranged from establishing relationships with research participants through case managers 25 and lay advocates 26 to changing the way that research teams engaged participants, which included leveraging different communication methods—for example, text messaging, 27 phone calls, 28 websites, 29 and video 30 —or locations, such as recruiting in churches. 31 Some strategies influenced the social context in which potential research participants made decisions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Wong e colaboradores 6 , o recrutamento por telefone, em comparação com o serviço de correio, pode melhorar a eficácia do recrutamento de 7% a 12%, com risco relativo de 1,66. Os resultados aqui apresentados corroboram esse e outros estudos randomizados que compararam o uso do consentimento telefônico com outros métodos 8,13 .…”
Section: Discussionunclassified
“…Ensaio clínico randomizado comparou o consentimento por telefone com o consentimento em consultas e mostrou que não houve diferença significativa nos níveis de compreensão das informações 8 . Outro ensaio clínico randomizado, que investigou o consentimento para rastreamento do câncer colorretal, apontou maior adesão à visita de triagem, bem como maior número de inclusões, no grupo de pacientes contatados por telefone, em comparação com aqueles contatados por carta 6 .…”
unclassified